The influence of baseline characteristics, treatment and depression on health-related quality of life in patients with multiple myeloma: a prospective observational study - Fischer, Julia; Knop, Stefan; Danhof, Sophia; Einsele, Hermann; Keller, Daniela; Loeffler, Claudia (BMC Cancer, 2022)
Background: Multiple myeloma (MM) is the third most common hematologic malignancy with increasing importance due to improving treatment strategies and long-term outcomes in an aging population. This study aims to analyse influencing factors on health-related quality of life (HRQoL), such as treatment strategies, participation in a clinical trial and patient characteristics like anxiety, depression, gender, and age. A better understanding of the individual factors in context with HRQoL could provide a helpful instrument for clinical decisions. Methods: In this prospective observational study, the HRQoL of MM patients with different therapies (first-line and relapse) was quantified by standardized questionnaires (EORTC QLQ-C30 and -MY20) in the context of sociodemographic data, individual anxiety and depressiveness (PHQ-4), and a selected number of clinical parameters and symptoms at defined time-points before, during, and after therapy. Results: In total, 70 patients were included in the study. The median age of the study cohort was 62 years. 44% were female and 56% were male patients. More than half of the patients were fully active with an ECOG 0. Global health status was significantly higher in patients with first-line treatment and even increased after start of therapy, while the pain level decreased. In contrast, patients with relapsed MM reported a decreasing global health status and increasing pain. Additionally, there was a higher global health status in less anxious/depressive patients. HRQoL decreased significantly after start of chemotherapy in the parameters body image, side effects of treatment, and cognitive functioning. Tandem stem-cell transplantation was not found to be a risk factor for higher impairment of HRQoL. Participation in a clinical study led to an improvement of most aspects of HRQoL. Among others, increased anxiety and depression, female gender, older age, impaired performance status, and recurrent disease can be early indicators for a reduced HRQoL. Conclusion: This study showed the importance of regular longitudinal assessments of patient reported outcomes (PROs) in routine clinical care. For the first time, to our knowledge, we were able to demonstrate a potential impact between participation in clinical trials and HRQoL. However, due to frequently restrictive inclusion criteria for clinical trials, these MM patients might not be directly comparable with patients treated within standard therapy concepts. Further studies are needed to clarify the relevance of this preliminary data in order to develop an individualized, patient-centred, therapy concept.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Depression; Multiple myeloma; Observational; Participation in clinical trials; Quality of life